Tindak Pidana Kekerasan dalam Rumah Tangga terhadap Perempuan Korban Pernikahan Dini Selama Pandemi Covid-19 - Yudha, Ahmad arie; Yunanto, Yunanto (Fakultas Syariah INSURI Ponorogo, 2023)
During the pandemic, the number of applications for marriage dispensation in Indonesia has increased. Marriages carried out when the man or woman as the prospective bride are underage are included in the category of violence against children. When a marriage is motivated by coercion or certain conditions, there will be high vulnerability in marriage, especially for women, this vulnerability includes the quality of health, vulnerability as a victim of domestic violence, education, and mental health. It is not only married women who are vulnerable, but the children of the marriage are also vulnerable. This research is a qualitative research whose implications are descriptive analytical. In connection with this approach, the type of normative juridical approach used is the legal approach. The results of this study are the factors behind the existence of violence against women victims of early marriage during the Covid-19 period, including the pandemic situation itself, job exposure, unequal programs related to a comprehensive understanding of sexual and reproductive health rights, as well as the presence of misuse of information. Proper legal protection for them is regulated in Law Number 23 of 2004 concerning the Elimination of Domestic Violence stipulates that during recovery victims will receive services in the form of health workers, social workers, companion volunteers and spiritual guides